Formação inicial de professores(as) pedagogos no contexto multilíngue de Foz do Iguaçu - Deus, Miriam de Oliveira Almeida de (2019)
This dissertation aims to reflect on how the Pedagogy course, offered at UNIOESTE, on the Foz do Iguaçu campus, has contributed to educate educators who work in the multilingual context of Foz do Iguaçu in public educational institutions that offer teaching. elementary II and medium. The choice of this theme is due to the understanding that public schools located in the triple frontier often receive the enrollment of several Spanish-speaking foreign students whose parents look for places in elementary school I, II and high school. The methodological approach chosen for its realization was based on a qualitative documentary-bibliographical analysis, which is exploratory and interpretative research, which focuses on studies on language policies and educational policies. Among the results obtained, it is emphasized that the critical and reflexive analysis outlined on the curricular matrix and the PPP of the Pedagogy course, made evident the existence of discussions about Language Policies, the specificities of the student living and studying at the triple frontier, and the multi/plurilingualism, as well as the commitment of this university with the specificities of the praxis to be performed by professionals working in this region of intense border traffic and, therefore, the documents that guide the operation of the course differ from other regions of Paraná and from the country itself. It is noteworthy that access to quality initial training is indispensable for the future educator to appropriate the theoretical and practical knowledge necessary to properly guide the teaching and learning process of both immigrants and school-age Brazilians, rethinking difficulties that arise daily. In addition, such documents make explicit the importance of developing classroom mediations in undergraduate education, ie, lengthening all initial education of teachers and supervised training when academics go to schools, with a continuous approach. of theory and practice. Another relevant point is focusing on the theoreticalmethodological orientation of the Pedagogy course that opted for the historicaldialectical materialism that explains society in general and, including education, as a guiding element in the formation of these professionals who need to be aware of the existence of and, above all, the need for objective intervention in the interests of the working class.